Diagnostic and Therapeutic Antibodies - George, Andrew J.T.; George, Andrew J.T.; Urch, Catherine E.; Urch, Catherine E. (Methods in Molecular Medicine,, 2000)
The use of monoclonal antibodies in treating disease has long held tantalizing promise, and the recent explosion of successful clinical trials-leading to the licensing of novel antibody-based therapeutic agents-has clearly demonstrated the power of recombinant antibody engineering, and greatly rejuvenated interest in their emergent clinical applications. In Diagnostic and Therapeutic Antibodies, a team of experts comprehensively reviews the theoretical and practical aspects of applying antibodies in both the laboratory and clinic. For general understanding, the book thoroughly introduces the basic science of the antibody molecule, including its structure and generation. Several novel in vivo applications of therapeutic antibodies are then presented to illustrate their special value in varied clinical settings. For those new to the field, there are readily reproducible methods for generating and purifying antibodies and for modifying them for clinical application, including how to measure their affinity and immunoactivity, and how to employ them in staining procedures and in a variety of in vitro assays. Timely and comprehensive, Diagnostic and Therapeutic Antibodies offers today‚s clinical researchers a concise introduction to the field, as well as a highly useful compendium of practical protocols that will greatly facilitate the application of these powerful new diagnostic and therapeutic agents.